Co-Delivery of Berberine Chloride and Tariquidar in Nanoliposomes Enhanced Intracellular Berberine Chloride in a Doxorubicin-Resistant K562 Cell Line Due to P-gp Overexpression - Giulia Vanti; Marcella Coronnello; Daniele Bani; Antonella Mannini; Maria Camilla Bergonzi; Anna Rita Bilia (MDPI AG, 2021)
The MDR phenomenon has become a major obstacle in the treatment of cancers, and among the strategies to reverse it, the inhibition of P-gp function and expression is essential to increase for effective anticancer drugs. In the present paper, the co-delivery of berberine chloride and tariquidar loaded nanoliposomes was investigated with the aim of enhancing solubility and improving desired effects for the antineoplastic drug and the P-gp inhibitor. Developed nanoliposomes were loaded with the electron-dense enzyme horseradish peroxidase, and analyzed by TEM to investigate their ability to enter in both K562 and K562/DOXO cell lines. Receptor-mediated endocytosis was evidenced for both cell lines. Nanoliposomes were loaded with tariquidar, berberine chloride, or both, maintaining chemical and physical characteristics-i.e., size, homogeneity, and encapsulation efficiency-and high suitability for parenteral administration. Tariquidar was able to reverse the MDR in the K562/DOXO cell line. Tariquidar- and berberine chloride-loaded nanoliposomes showed a significant increase of berberine chloride accumulation in tumor cells, which could be correlated with resensitization of the resistant cells to the antitumor agent. These results suggest that the co-delivery of the P-gp inhibitor, tariquidar, and the cytotoxicity inducer, berberine chloride, looks like a promising approach to overcome the MDR.